Current status of parenteral nutrition and enteral nutrition application: an assessment of nutritional prescriptions from 59 hospitals in the People’s Republic of China - Han G; Yu ZW; Ma K (Dove Medical Press, 2015)
Gang Han, Zhenwei Yu, Ke Ma Sir Run Run Shaw Hospital, College of Medicine, Zhejiang University, Hangzhou, People’s Republic of China Purpose: The aim of the study reported here was to assess the use of parenteral nutrition (PN) and enteral nutrition (EN), and the prevalence of PN and EN formulas, in the People’s Republic of China. Methods: Fifty-nine hospitals in the People’s Republic of China participated in a nutrition survey. The resulting information on nutritional support was analyzed. Results: We received 379,584 nutritional-support prescriptions over 40 days in 2013. PN provided approximately 63.2% and EN provided approximately 36.8% of nitrogen intake. PN provided 63.5% and EN provided 36.5% of lipid intake. There were obvious differences in nitrogen and lipid intake between PN and EN in different regions, departments, and diseases. The percentage of nourishment provided by PN in different regions was highest in Chengdu, followed by the Beijing, Guangzhou, and Hangzhou areas. The percentage of nourishment provided by PN in different departments was highest in general surgery, followed by gastroenterology and the intensive care unit. The percentage of nourishment provided by PN in different diseases/conditions was highest in acute pancreatitis, followed by cancer, and burns. The main source of nitrogen in PN was balanced amino-acid preparations, and in EN, it was protein. The main source of lipids in PN was long- and medium-chain triglyceride lipid emulsion injection. Conclusion: Despite recent improvements in the application of nutritional support in the People’s Republic of China, a much higher percentage of nitrogen and lipids is delivered through PN than through EN. Furthermore, there are marked regional, departmental, and disease-based differences in the selection of PN versus EN. The rationale for use of nutritional support needs to be improved. Keywords: nutrition survey, prescription, nutritional support, amino-acid preparations, lipid emulsion